Comparing Digital Media and Motivation Correlation with PAI Aqidah Akhlak Competence at MA and MTs Ar-Rahmaniyah NW Senyiur - Ayatullah, Ayatullah (ISLAMIKA, 2026)
This study is motivated by the limited research on the interconnected roles of digital media use and learning motivation in shaping Aqidah Akhlak competence, despite their increasing relevance in Islamic education. The study aims to analyze cross-level differences in digital media utilization, examine the correlation between learning motivation and Aqidah Akhlak competence, and evaluate the combined predictive influence of digital media use and learning motivation among students at MTs and MA Ar-Rahmaniyah NW Senyiur. Employing a quantitative correlational design, it involved a purposive sample of 61 students—35 Grade 7 MTs students and 26 Grade 10 MA students. Data were collected using validated questionnaires on digital media usage and learning motivation, alongside a standardized Aqidah Akhlak competence test, and were analyzed using descriptive statistics, Pearson product–moment correlation, and multiple regression to determine relational patterns and predictive strengths. The findings reveal significant cross-level distinctions: MA students demonstrate more advanced and academically oriented digital media practices, higher levels of learning motivation, and stronger correlations between these variables and Aqidah Akhlak competence. Motivation emerges as the strongest predictor at both levels, while digital media exerts greater predictive influence at the MA level, and the combined model explains more variance in competence among MA students, indicating greater integration of digital and motivational factors as students mature. The study concludes that digital engagement and learning motivation play crucial roles in enhancing moral comprehension, with implications for strengthening digital pedagogy and motivational strategies in Islamic education. Future research is recommended to expand the sample, incorporate qualitative insights, and examine longitudinal effects.